Aggregation‐Induced Emission and Retention of Crystal Chiral Information of Tetraphenylethylene Incorporated by Polysaccharides in Water. Issue 8 (1st April 2020) - Hino, Shodai; Sugikawa, Kouta; Kawasaki, Riku; Funabashi, Hisakage; Kuroda, Akio; Ikeda, Atsushi
Abstract: Polysaccharides, such as pullulan and λ‐carrageenan, can incorporate tetraphenylethylene derivatives through self‐aggregation in water by a high‐speed vibration milling method, which cannot be done by sonication and heating methods. Aggregation‐induced emission is observed from the tetraphenylethylene‐polysaccharide complexes. Furthermore, the tetraphenylethylene self‐assembled into polysaccharides is able to preserve the initial helical chirality ( M ‐ or P ‐helicity) of the crystals in water after ball milling. Intracellular uptake of the polysaccharide‐complexed tetraphenylethylene derivative with a phenol unit by HeLa cells is enhanced compared with that without the phenol unit. Abstract : Twist and shout : Water‐soluble tetraphenylethylene‐polysaccharide complexes prepared by a high‐speed vibration milling method maintain the initial helical chirality (M‐ or P‐helicity) of the tetraphenylethylene crystals in water.